Supra-Annular Mitral Implantation of Melody Valve: Minimizing Left Ventricular Outflow Tract Obstruction. Issue 2 (March 2019) - Stephens, Elizabeth H.; Tannous, Paul; Nugent, Alan W.; Hauck, Amanda L.; Forbess, Joseph M.
Utilization of the Melody valve for mitral valve replacement has been previously reported; however, left ventricular outflow tract obstruction is a frequent concern. In this report, a technique for supra-annular placement of the Melody valve in the mitral position is described which will minimize the risk of left ventricular outflow tract obstruction.